THE SHIFT IN CLOTHING SHOPPING PREFERENCES: AN ANALYSIS OF ONLINE &. OFFLINE CONSUMER BEHAVIOR IN THE VINDHYA REGION - Agarwal, Pranjal; Singh, Chandan; Mishra, Shekhar Kumar; Garg, Ankit Kumar; Soni, Kartik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the shift in clothing shopping preferences from offline to online platforms within the Vindhya region. With the rapid expansion of e-commerce and changing consumer behaviors, understanding regional variances in shopping preferences has become increasingly crucial. This study investigates the factors influencing consumer choices between online and offline shopping, focusing on convenience, pricing, variety, and local cultural factors. Utilizing both quantitative surveys and qualitative interviews, the research highlights the evolving landscape of clothing retail in the Vindhya region. The findings reveal a significant trend towards online shopping, driven by the convenience of home delivery and a broader selection of products. However, offline shopping remains relevant due to the importance of tactile experiences and immediate gratification. This analysis provides valuable insights for retailers and marketers aiming to tailor their strategies to regional consumer preferences, contributing to the broader discourse on retail evolution in emerging markets.